Biomarkers Used in Screening Patients for Diabetic Nephropathy and Their Target Indicators - Asila, Murodova; Francis, Donaldo; Xalbayeva, Zubayda (American Journal of Bioscience and Clinical Integrity, 2026)
Diabetic nephropathy continues to be a common cause of chronic kidney disease and end-stage renal disease (ESRD) globally. Early identification using reliable biomarkers is necessary for intervention preventing irreversible kidney injury. We review established and novel biomarkers that have the potential to screen patients with diabetes for nephropathy, and assess the diagnostic accuracy, predictive ability and practical application of these predictors. Urinary albumin excretion, albumin-to-creatinine ratio, serum creatinine levels and estimated glomerular filtration rate (eGFR) are traditional measures still routinely used for screening purposes. New biomarkers such as cystatin C, neutrophil gelatinase-associated lipocalin, kidney injury molecule-1, transforming growth factor-β and inflammatory cytokines offer the advantage of earlier detection of tubular and glomerular injury. The findings suggest that when using the conventional markers and emerging markers of sensitivity for risk assessment are enhanced. End points used for screening are microalbuminuria, lowered GFR, structural kidney damage and risk of progression. Novel multiple biomarker panel for the early detection of end-stage renal disease in patients with diabetes. Diabetic nephropathy (DN) is a relentlessly progressive renal disease in diabetes mellitus (DM) that accounts for an increasing proportion of chronic kidney failure globally. Successful screening requires sensitive and specific biomarkers that distinguish early structural and functional kidney alterations prior to the development of irreversible damage. This review investigates common and novel laboratory markers used in simple and more complex screening protocols, with particular regard to the clinical targets addressed and their prognostic relevance. Traditional markers including U ACR and eGFR only offer fundamental evaluation of glomerular function and filtration efficiency. Other biomarkers such as cystatin C, neutrophil gelatinase-associated lipocalin, kidney injury molecule-1 and pro-inflammatory mediators can detect more subtle tubular injury and early fibrogenic activity. There is evidence for an integrated biomarker approach to increase diagnostic accuracy, improve risk prediction, and aid early treatment. Estimation of optimal target values for each indicator is necessary to retard the progression of diabetic disease and minimize the long-term consequences on the kidney and cardiovascular system.